The Effect of Communication on Improving Employee Performance in the Karawang District Manpower and Transmigration Department - Tungga, Riananda Dwismara; Solehudin, Solehudin; Nadeak, Banuara (JEM17: Jurnal Ekonomi Manajemen, 2024)
The purpose of this study is to determine the effect of employee communication on the performance of employees of the Ministry of Manpower and Migration of Karawang District. Communication acts as a process and medium for exchanging information, ideas, solutions, and opinions between superiors, subordinates, or co-workers. In addition, communication also plays a role in creating a harmonious work environment because every employee feels connected so that cooperation while in the office is well-guaranteed. This type of research is quantitative and uses descriptive and confirmatory research methods. The sample size for this study is 75. In this study, cross sampling is used. A multi-factor analysis method was used in this study. The results showed the effect of communication on the performance of the employees of the Department of Labor and Migration of Karawang District. Keywords: Communication, Employee Performance